Attitudinal factors associated with drink counting. (14th March 2021) - Booth, Leon; Jongenelis, Michelle I.; Drane, Catherine; Miller, Peter G.; Chikritzhs, Tanya; Hasking, Penelope; Hastings, Gerard; Thorn, Michael; Pettigrew, Simone
Abstract: Introduction: 'Count your drinks' is a protective behavioural strategy (PBS) that has been found to be effective in reducing alcohol consumption. Previous research has shown that females, older people and low‐risk drinkers are more likely to use this strategy, but little is known about the attitudinal factors associated with engaging in drink counting. This information is important for developing effective interventions to encourage use of this PBS. The aim of this paper was to assess whether the following attitudinal factors are associated with frequency of enactment of the 'Count your drinks' PBS: (i) perceived ease of use; (ii) perceived effectiveness; (iii) personal relevance; and (iv) believability. Methods: A total of 683 Australian drinkers completed an online survey assessing demographic variables, alcohol consumption, frequency of drink counting and attitudes to the 'Count your drinks' PBS. A hierarchical regression analysis was used to determine whether the attitudinal factors were associated with frequency of enactment after controlling for demographic and alcohol‐related factors. Results: Attitudes to the 'Count your drinks' PBS accounted for 28% of the variance in reported frequency of drink counting. Perceptions of personal relevance, ease of use and effectiveness were found to be significantly associated with frequency of enactment. Discussion and Conclusions: Interventions designed to encourage drinkers to count their drinks should aim to increase the perceived personal relevance, ease of use and effectiveness of this strategy.